2003
DOI: 10.1152/jn.00180.2003
|View full text |Cite
|
Sign up to set email alerts
|

Flash Photolysis Reveals a Diversity of Ionotropic Glutamate Receptors on the Mitral Cell Somatodendritic Membrane

Abstract: Lowe, Graeme. Flash photolysis reveals a diversity of ionotropic glutamate receptors on the mitral cell somatodendritic membrane. J Neurophysiol 90: 1737-1746, 2003. First published April 30, 2003 10.1152/jn.00180.2003. It is widely held that the soma and basal dendrites of olfactory bulb mitral cells receive exclusively inhibitory synaptic input from local interneurons. However, the mitral somatodendritic membrane exhibits immunoreactivity for a variety of glutamate receptors, and blocking GABA receptors unm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 55 publications
0
27
0
Order By: Relevance
“…The presence of such astrocytic functional domains (42) suggests that it is likely that two different types of astrocytes are responsible for SOCs and SICs. Indeed, SICs were not observed in mitral cells, whereas their dendrites are covered by functional glutamate receptors (43), and synchronous SOCs, but not synchronous SOCs and SICs, were detected in paired recordings of mitral and granule cells. However, we cannot rule out the possibility that a single astrocyte releases GABA and glutamate separately at different and spatially distant release sites.…”
Section: Discussionmentioning
confidence: 92%
“…The presence of such astrocytic functional domains (42) suggests that it is likely that two different types of astrocytes are responsible for SOCs and SICs. Indeed, SICs were not observed in mitral cells, whereas their dendrites are covered by functional glutamate receptors (43), and synchronous SOCs, but not synchronous SOCs and SICs, were detected in paired recordings of mitral and granule cells. However, we cannot rule out the possibility that a single astrocyte releases GABA and glutamate separately at different and spatially distant release sites.…”
Section: Discussionmentioning
confidence: 92%
“…The reason for this may be that dendritic tufts are deeply embedded in the glomerular neuropil, perhaps enclosed in glial microcompartments (Kasowski et al, 1999). To overcome diffusion barriers, we employed flash photolysis of caged glutamate, a method capable of rapidly and efficiently activating AMPA receptors in olfactory bulb slices (Lowe, 2003). As in the olfactory nerve shock experiments, either dCK or APV were added to the bath to eliminate NMDA receptor currents and isolate the AMPA/kainate current.…”
Section: Glutamate Uncaging Activates a Polyamine-sensitive Epsc In Ementioning
confidence: 99%
“…Thus, fast glutamatergic neurotransmission is critical for ET cell circuit operations in both presynaptic and postsynaptic contexts. Determining the specific physiological properties of glutamate receptors expressed by ET cells is an important step towards a better understanding of their function.Ionotropic glutamate receptors are expressed in a diversity of forms (Dingledine et al, 1999), and recent studies have indicated localization of different subtypes in distinct compartments of olfactory bulb neurons (Trombley and Shepherd, 1993;Montague and Greer, 1999;Blakemore and Trombley, 2003;Lowe, 2003;Horning et al, 2004). In the glomerular layer of the bulb, both NMDA and AMPA/kainate receptors have been characterized by immunolabeling (Giustetto et al, 1997;Montague and Greer, 1999;Sassoe-Pognetto et al, 2003) and physiological studies (Ennis et al, 1996;Aroniadou-Anderjaska et al, 1997;Keller et al, 1998;Edwards and Michel, 2003;Murphy et al, 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As the primary excitatory neurotransmitter in the mammalian CNS, glutamate ͑Glu͒ derivatives such as 4-methoxy-7-nitroindolinyl-caged L-glutamate ͑MNI-Glu͒ have proven most useful for studying synaptic integration. 2,9 Bathing an acute brain slice in artificial cerebrospinal fluid ͑aCSF͒ containing MNI-Glu has no observable effect. However, application of near-UV excitation rapidly excitation.…”
Section: Introductionmentioning
confidence: 99%